Novel derivatives of Costus igneus towards potentiality against diabetes mellitus receptors: ADME/Tox profiling, Computational Docking, and Molecular Dynamics Simulation study - Mansi Yadav; Poonam Yadav; Jaya Parkash Yadav; Sudhir Kumar Kataria (Journal of Taibah University for Science)
Costus igneus has been practiced to alleviate a range of human ailments and the substantial vision was to explore potential bio-active compounds of  Costus igneus to better comprehend the underlying mechanism in the management of diabetes. In-silico  approach using AutoDock and Desmond, the anti-diabetic  efficacy of discovered phytochemicals was evaluated. The best-docked were chosen for simulation studies. The molecular dynamic modelling showed that the complexes of ligands with receptors were stable during a time of 100 ns, which further confirmed and enhanced their significant binding affinity. According to docking scores and simulation studies, these phytocompounds could be targeted to garner efficient preventive medications for diabetes from a biological source using contemporary technology, and further in vivo and in vitro research of these compounds may be encouraged in the search for a potent treatment for the disease.